If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -1x + -18 + 2x + 4 = 6x + 24 Reorder the terms: -18 + 4 + -1x + 2x = 6x + 24 Combine like terms: -18 + 4 = -14 -14 + -1x + 2x = 6x + 24 Combine like terms: -1x + 2x = 1x -14 + 1x = 6x + 24 Reorder the terms: -14 + 1x = 24 + 6x Solving -14 + 1x = 24 + 6x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-6x' to each side of the equation. -14 + 1x + -6x = 24 + 6x + -6x Combine like terms: 1x + -6x = -5x -14 + -5x = 24 + 6x + -6x Combine like terms: 6x + -6x = 0 -14 + -5x = 24 + 0 -14 + -5x = 24 Add '14' to each side of the equation. -14 + 14 + -5x = 24 + 14 Combine like terms: -14 + 14 = 0 0 + -5x = 24 + 14 -5x = 24 + 14 Combine like terms: 24 + 14 = 38 -5x = 38 Divide each side by '-5'. x = -7.6 Simplifying x = -7.6
| a-6b+2c+a-6b+n-2c= | | 9y+3=27 | | 4b+25=9b | | 6(4-1)-5(z+8)=16(z+1) | | y=-(1)-3 | | y=-(0)-3 | | y=-(-1)-3 | | 4b+5x=2x | | -8(t-5)-(t+4)=9 | | 2x+10=27 | | 7.7(-9+2x)=-49 | | y=6(5)-8 | | x=9x-12 | | y=6(1)-8 | | 12(2x-5)=24x+16 | | -(3y+2)-(-2y-8)=5 | | y=6(-1)-8 | | 6+2(x-1)=1-3(x-6) | | 4+6(x-2)=1-5(x-1) | | -49=3x+3x-7 | | -(4y+1)-(-3y-6)=4 | | 12+-2a=2 | | 9ln(8x)=54 | | 2y+10(2)=-16 | | 2y+10(-3)=-16 | | -8+2x-4x=-18 | | -5(3n+2)=10 | | ln(x)+ln(x+4)=0 | | 15y-3=29-y | | 17b-8=0 | | x-18+2(x+2)=6x+24 | | 4(4x-1)=2(8x+6) |